Semiconductor gas sensor - Fang, Peiyuan (2015)
Over the past few years, semiconductors are very attractive materials that are commonly used to make electronic devices such as Bipolar Junction Transistor (BJT), Metal Oxide Semiconductor Field Effect Transistor and Complementary Metal Oxide Semiconductor Transistor (CMOS), which consist of N-MOSFET and P-MOSFET, etc. In this project, there are two parts, the first part consists of High Electron Mobility Transistor (HMET) structure, 2 DEG properties, Gallium Nitride properties and Molecular Beam Expitaxy (MBE) studies before proceeding to device development. Hall effect measurement and Atomic Force Microscopy (AFM) results will be analysed to have a better understanding on the electrical characterization. Using Hall effect measurements, it is shown that samples V234 and V648 exhibit reasonable mobility as compared to the other samples. Using Atomic Force Microscopy (AFM), it is shown that sample V234 offer better morphology and smooth surface. The second part consists of how the devices respond to the gases when they are exposed in a closed chamber. Because of the surface reaction, the device resistance level will either increase or decrease depending on gases that are inserted. Currently, the gases that were used for testing are Carbon dioxide (C02), Nitrogen oxide and Ammonia. During the experiment, we found that Gallium Nitride HEMT can be used as a gas sensor when operating at 150 oC. In this study, it is shown that with higher concentration of C02, there is more reaction on the surface and hence the resistance will decrease more as compared to lower concentration. To overcome this issue and functionalize the surface, we may need to use starch/ polyethylenimine on the device surface for C02 sensing with lower concentration.